A novel near-infrared xanthene-based fluorescent probe for detection of thiophenol in vitro and in vivo. (6th October 2020) - Wu, Yongquan; Shi, Aiping; Liu, Huiying; Li, Yuanyan; Lun, Weican; Zeng, Hong; Fan, Xiaolin
Abstract : A novel near-infrared xanthene-based fluorescent probe for detection of thiophenol in living cells and mice. Abstract : Thiophenol (or PhSH) is widely utilized for producing pesticides, dyes, and pharmaceuticals. However, high-concentration thiophenol not only has adverse effects on living organisms, but also causes environment pollution. Herein, we designed and synthesized a novel near-infrared (NIR) xanthene-based fluorescent probe (NOF ) for real-time detection of thiophenol in vitro and in vivo . The probe NOF had good sensitivity and selectivity, and a fast response towards thiophenol. The thiophenol-sensing mechanism was verified using high resolution mass spectroscopy (HR-MS) and density functional theory (DFT) calculation. The probe NOF was also successfully applied to detect thiophenol in real water samples. Finally, owing to its NIR-emitting properties, it was successfully used for NIR fluorescence imaging of thiophenol in living cells and mice.